Strategi Mitigasi Risiko Industri Rumahan Pembuatan Kue Basah dan Snackbox Untuk Meningkatkan Keberlanjutan Usaha Pada Mulia Snackbox & Cookies - Fiqi Ardi Abdurahman Masdar; Fajar Fajar; Ari Assrishan Sosh Mantoro; Muhammad Irfan Fauzan; Alfiana Alfiana (Indo Publishing, 2026)
The sustainability of home industries is often threatened by risk management that is still intuitive and reactive. This study aims to formulate a risk mitigation strategy at Mulia Snackbox & Cookies using the ISO 31000:2018 framework. Using a descriptive qualitative method, the study identified 35 risk events spread across seven operational segments. Evaluation through the Likelihood and Impact matrix maps a number of crucial risks at the priority level, consisting of 1 Extreme risk (utility disruption) and 12 High risks (dominated by fluctuations in raw material prices and operational techniques). The formulated mitigation strategies include Risk Reduction (provision of energy reserves and routine machine maintenance), Risk Sharing (negotiation of corporate contract clauses), and Risk Avoidance (disciplined financial segregation). The results of the study prove that ISO 31000 adaptation provides a structured approach to improving operational resilience and long-term business financial stability.